Persepsi Masyarakat terhadap Implementasi Sistem Informasi Layanan Elektronik Terintegrasi Online (SILETON) di Disdukcapil Kabupaten Agam - Rahmayanti, Anisa (Jurnal Teori dan Riset Administrasi Publik, 2025)
Public perception of the Integrated Online Electronic Service Information System (SILETON) service at the Population and Civil Registration Office of Agam Regency is still diverse. There are several factors that influence public perception of SILETON services. This study aims to identify public views on SILETON services and the factors that influence public perception of SILETON services. The research method used is a descriptive qualitative approach, with data collection through interviews and direct observation. The results of the study indicate that this service has provided convenience and efficiency in managing population administration documents. SILETON is considered a useful innovation, especially because it can save time, costs, and energy, and allows people to access services flexibly without having to come directly to the Disdukcapil office. However, there are still several factors that influence public perception of the use of SILETON services, including uneven networks in remote areas, technical factors in the SILETON application, the level of community education, and the lack of socialization carried out by the Population and Civil Registration Office. Keywords: Public Perception, Public Services, Population Administration, Service Digitalization, Integrated Online Electronic Service Information System (SILETON).